Groundwater Flow Modeling at Sejorong Watershed, Sumbawa,West Nusa Tenggara, Indonesia - Doni Prakasa Eka Putra; Adelide Asriati Sekar Rianda; Wahyu Wilopo (Journal of Applied Geology, 2020)
ABSTRACT. Batu Hijau mine pit is known as one of the largest copper pit mine in Nusa Tenggara Barat, Indonesia. Similiar as other copper mine pits in Indonesia, This site also faces acid mine water (AMD) problem. Based on the mine management plan, the AMD generated from this pit is being collected into Santong ponds in the southwest of the pit located in the upstrean area if Sejorong watershed. By the next decade, Batu Hijau mine will be in the closure mine period and it is important to understand the probable move- ment of AMD under the Santong ponds whether the AMD leaked to groundwater or not. This research aims to develop a numerical model of groundwater ﬂow and predict the movement of AMD by applying particle tracking method. Secondary and primary data of geology, hydrology, and hydrogeology. Also, groundwater pumpage discharge infor- mation was collected and analysed to develop hydrogeological conceptual model and the numerical model. The conceptual model of hydrogeological system in the research area is known to be built on unconﬁned aquifer system from a combination of weathered and fractured volcanic rocks in the upstream to middle part of watershed and majorly by allu- vial and coastal deposits in the downstream area. The thickness of aquifer is vary between 20 to about 300 m and divide into 5 layers in the numerical model, with hydraulic conduc- tivity ranges between 5 to 100 m/day and groundwater recharge is vary between 180 to 700 mm/year from downstream to upstream of watershed. Groundwater ﬂow boundaries in the Sejorong watershed are mainly controlled by topographical feature as water divide boundaries and the existing of Sejorong parennial rivers in the middle of this watershed. Steady state particle tracking results from the numerical groundwater ﬂow model show AMD from Santong ponds may migrate in groundwater only to a distance of about 500 m to the downstream and therefore it is unlikely that AMD seepages from Santong pond may contaminate water in the production wells.